2021
DOI: 10.1021/acs.inorgchem.1c00225
|View full text |Cite
|
Sign up to set email alerts
|

Different Chemical Environments of [Ge4Se10]4– in the Li+ Compounds [Li4(H2O)16][Ge4Se10]·4.33H2O, [{Li4(thf)12}Ge4Se10], and [Li2(H2O)8][MnGe4Se10], and Ionic Conductivity of Underlying “Li4Ge4Se10

Abstract: The crystalline selenido germanates [Li4(H2O)16]­[Ge4Se10]·4.3H2O (1), [{Li4(thf)12}­Ge4Se10] (2), and [Li2(H2O)8]­[MnGe4Se10] (3) (thf = THF = tetrahydrofuran) were obtained by an extraction of a glassy ternary phase of the nominal composition Li4Ge4Se10 (=Li2S·2GeSe2) with water (1) or THF (2) and slow evaporation of the solvent or by being layered with MnBr2 in H2O/MeOH (3), respectively. The compounds contain known selenido germanate anions, however, for the first time with Li+ counterions. This is especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…They are mostly formed from the elements and/or simple binary precursors by the Methods A–C and E, resulting in regular adamantane-type anions with mostly (alkaline) metal or ammonium counterions. 253–282 In a unique synthetic approach, it was also shown that those clusters can be made electrochemically using a Sn 2 Se 3 cathode in a [Et 4 N]Br electrolyte solution in ethane-1,2-diamine to form [Et 4 N] 4 [Sn 4 Se 10 ] ( 517 ). 283…”
Section: Variety Of Compositions and Synthesesmentioning
confidence: 99%
See 1 more Smart Citation
“…They are mostly formed from the elements and/or simple binary precursors by the Methods A–C and E, resulting in regular adamantane-type anions with mostly (alkaline) metal or ammonium counterions. 253–282 In a unique synthetic approach, it was also shown that those clusters can be made electrochemically using a Sn 2 Se 3 cathode in a [Et 4 N]Br electrolyte solution in ethane-1,2-diamine to form [Et 4 N] 4 [Sn 4 Se 10 ] ( 517 ). 283…”
Section: Variety Of Compositions and Synthesesmentioning
confidence: 99%
“…Two examples also showcase the possibility of creating manganese linked adamantane-type structures by Method E, the extraction of a solid created from a melt of simple precursors ( 1007–1008 ). 275,282 This led to the only example of a tellurium adamantane in network structures ( 1007 ).…”
Section: Variety Of Compositions and Synthesesmentioning
confidence: 99%